Proportion of Patients With Hypertension Resolution Following Adrenalectomy for Primary Aldosteronism: A Systematic Review and Meta‐Analysis. Issue 12 (19th October 2016) - Benham, Jamie L.; Eldoma, Maysoon; Khokhar, Bushra; Roberts, Derek J.; Rabi, Doreen M.; Kline, Gregory A.
Abstract : Unilateral primary aldosteronism (PA) is often treated with adrenalectomy, but hypertension resolution rates are variable. A valid estimate of the postoperative normotension rate is necessary to inform the utility of PA testing and treatment. The authors searched MEDLINE In‐Process & Other Non‐Indexed Citations, Embase, and Cochrane Central Register of Controlled Trials. Prospective adult cohort studies with surgically treated PA that reported resolution of hypertension without the aid of medications were included. Among 2620 abstracts identified by the search, 25 studies in the systematic review with data on 1685 patients were investigated. The pooled proportion of normotension following adrenalectomy was 52% (95% confidence interval, 0.44–0.60). Meta‐regression demonstrated a significant negative association between length of follow‐up and proportion of normotension, with normotension dropping by 6.7% per year of follow‐up (coefficient −0.006; 95% confidence interval, −0.01 to 0.002). Overall, approximately half of the patients experienced hypertension resolution, although this outcome may not be durable in all patients.